2005
DOI: 10.1007/s00018-005-5328-4
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α upregulates adenosine 2b (A2b) receptor expression and signaling in intestinal epithelial cells: a basis for A2bR overexpression in colitis

Abstract: Adenosine is an endogenous signaling molecule upregulated during inflammatory conditions. Acting through the A2b receptor (A2bR), the predominant adenosine receptor in human colonic epithelia, adenosine has been directly implicated in immune and inflammatory responses in the intestine. Little is known about expression and regulation of A2bR during inflammation. Tumor necrosis factor alpha (TNF-alpha) is highly upregulated during chronic and acute inflammatory diseases. This study examined the expression of A2b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
116
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(125 citation statements)
references
References 37 publications
8
116
0
Order By: Relevance
“…All mice that were fed 3% DSS for 7 days developed signs of severe colitis (clinical score: 9.4 Ϯ 1.0; histological score: 9.1 Ϯ 2.3), presented as bloody diarrhea and weight loss. Consistent with our previous observations (9), A 2B AR mRNA levels increased 2.3 Ϯ 0.3-fold (*p Ͻ 0.05), compared with control mice that received water (Fig. 5A).…”
Section: Tnf-␣ Does Notsupporting
confidence: 92%
See 3 more Smart Citations
“…All mice that were fed 3% DSS for 7 days developed signs of severe colitis (clinical score: 9.4 Ϯ 1.0; histological score: 9.1 Ϯ 2.3), presented as bloody diarrhea and weight loss. Consistent with our previous observations (9), A 2B AR mRNA levels increased 2.3 Ϯ 0.3-fold (*p Ͻ 0.05), compared with control mice that received water (Fig. 5A).…”
Section: Tnf-␣ Does Notsupporting
confidence: 92%
“…In our previous studies, we observed the up-regulation of A 2B AR by TNF-␣ in colonic epithelial cells and in the DSS mouse model of colitis (9). Using a pFLR7 promoter-reporter construct that contained either the 1.4-kb and 2.5-kb fragments of the A 2B AR promoter, we found that TNF-␣ did not increase A 2B AR promoter activity (Fig.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The A2B adenosine receptor differs from the other adenosine receptors by its relative low affinity for adenosine (Feoktistov and Biaggioni, 1997). A2B is transcriptionally induced by hypoxia-inducible factor-1a activation (Eltzschig et al, 2003;Feoktistov et al, 2004), TNF-a, IL-1b, IFN-g and extracellular adenosine (Xaus et al, 1999;Kolachala et al, 2005;St Hilaire et al, 2008).…”
Section: Adenosine Receptorsmentioning
confidence: 99%